Локальные и сезонные явления гипоксии на дне Севастопольских бухт и их влияние на макробентос - (:unkn) unknown (My University, 2011)
В трёх точках севастопольского побережья (Севастопольская бухта, внешний рейд, бухта Омега) в течение года выполнены полярографические исследования вертикального распределения кислорода и сероводорода в поверхностном слое грунта и сборы макробентоса. Отобрано 15 колонок грунта для химических анализов и 23 пробы бентоса. В зависимости от расположения точки и сезона года граница появления H2S менялась от поверхности грунта до глубины >60 мм. Составлен ряд данных, ранжированный по глубине появления сероводорода. Этот ряд приняли как показатель степени гипоксии и сопоставили с общей численностью бентоса, с обилием его основных групп. Общая численность макробентоса снижается по мере приближения границы сероводорода к поверхности грунта. Среди таксономических групп это же выявилось у Annelida и Bivalvia. В то же время, реакция Gastropoda различалась в отдельных точках, а обилие Crustacea повышалось с приближением H2S к поверхности грунта. Для объяснения влияния гипоксии на макробентос необходимо учитывать видовой состав каждой группы и экологические свойства каждого вида.
The events of local and seasonal hypoxia at the bottom of the Sevastopol bays and their influence on macro- benthos
Voltammetric measurements of the oxygen and sulfide content in the upper bottom sediments and studies of macrobenthos have been carried out for three sites of the Sevas- topol coastal zone. In total, 15 samples for the sediment cores for voltammetric analyses and 23 samples for studies of benthos have been collected. The depth of the H2S onset varied from the ground surface to 60mm depending on the site location and the season of sampling. The data have been ranged according to the depth of the hydrogen sulfide appearance that has been considered as an indicator of the degree of hypoxia. It was compared with total benthos abundance and with the abundance of individual groups of benthos. The total macrobenthos abundance decreases with the upward shift of the hydrogen sulfide onset in the bottom sediments. It is also true for Annelida and Bivalvia individual abundance. At the same time, Gastropoda reaction has been different, and Crustacea abundance has increased with H2S approaching to the surface of the bottom sediments. The group species composition and every species ecological properties must be taken into consideration for finding the explanations.
Keywords: Черное море; гипоксия; сероводород; численность макробентоса